IMPLEMENTASI METODE EXTREME PROGRAMMING PADA SISTEM INFORMASI REPOSITORI SKRIPSI DI PERPUSTAKAAN UNIVERSITAS PRABUMULIH - Illahi, Kur Niayu; Suhartini, Suhartini; Fajriyah, Fajriyah (Badan Penelitian dan Pengabdian Masyarakat (BP2M) STMIK Syaikh Zainuddin NW Anjani, 2023)
Repository information system is a system used to manage the filing of student thesis collections to make them neater, safer, easier to manage and accessible again. At the Prabumulih University Library, the process of accessing theses is still done manually by searching for and reading available theses at the Prabumulih University Library. This is the background for this research. In collecting data, researchers used qualitative descriptive methods including direct observation, interviews and literature study. So that data is obtained that there is no available access that makes it easy for students to read the full text of the thesis online. The result of this research is in the form of a web-based thesis repository information system design which is expected to help resolve the problems that occur. Using a repository information system can help library staff and students in obtaining and managing student thesis collections carefully, precisely and in a faster time. In designing this system, it uses the Extreme Programming (XP) method with Unified Modeling Language (UML) system modeling tool. The system is created by using the PHP language and the MySQL database server. Keywords: Extreme Programming, Information System, Repository, Thesis